Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1017/s0007114508894354
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary data about the influence of vitamin D status on the loss of body fat in young overweight/obese women following two types of hypocaloric diet

Abstract: The loss of weight was analysed in a group of sixty overweight/obese women of childbearing age (20-35 years) according to their initial vitamin D status. Subjects were randomly assigned to one of two slightly hypocaloric diets: Diet V, in which the consumption of vegetables was increased, or Diet C, in which the relative consumption of cereals (especially breakfast cereals) was increased. Dietetic, anthropometric and biochemical data were collected at the start of the study and again at 2 weeks after dividing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
2
26
0
3
Order By: Relevance
“…Recent data from an overweight/obese women's study have suggested that women with high 25(OH)D levels respond more positively to hypocaloric diets and lose more body fat than women with low 25(OH)D levels (35). There is evidence that weight loss is probably the most effective treatment of PCOS women at the moment (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from an overweight/obese women's study have suggested that women with high 25(OH)D levels respond more positively to hypocaloric diets and lose more body fat than women with low 25(OH)D levels (35). There is evidence that weight loss is probably the most effective treatment of PCOS women at the moment (36).…”
Section: Discussionmentioning
confidence: 99%
“…In the RCTs by Ortega et al (2008) higher vitamin D at baseline (450 nmol/l; mean value: 85.9±44.4) resulted in greater fat loss and preservation of lean tissue over 2 weeks. This was partially supported by a long-term RCT where higher vitamin D at 6 months (median for tertiles ¼ 14.5, 21.2 and 30.2 ng/ml) predicted greater weight loss at 2 years (Shahar et al, 2010).…”
Section: Indirect Evidencementioning
confidence: 94%
“…[1][2][3][4][5][6][7][8][9][10] Although this association has been attributed to increased storage of 25(OH)D in fat tissue or potential lifestyle differences between obese and nonobese populations, 11,12 evidence from epidemiologic, [1][2][3][4][5][6][7][8][9][10] weight loss, [13][14][15][16][17] and in vitro/ animal studies [18][19][20][21][22][23][24] suggests that 25(OH)D might be involved in weight regulation. Vitamin D receptors (VDR) are present on human adipocytes.…”
mentioning
confidence: 99%